2022
DOI: 10.1007/s13399-022-03273-8
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the metabolic features of purple non-sulfur bacteria for waste carbon utilization and single-cell protein synthesis

Abstract: In recent years, single-cell protein (SCP) has been considered a promising aquaculture feed to cope with the growing issue of food security. SCP is derived from microbes including algae, yeasts, and bacteria. Algae and yeasts have been comprehensively studied as SCP sources in the last few years. However, their large-scale application is not yet economical. Recently, the use of purple non-sulfur bacteria (PNSB) has been realized as a sustainable source of SCP. PNSB display unique metabolic features that distin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 131 publications
0
2
0
Order By: Relevance
“…The maximum protein percentage of 34% is lower compared to studies conducted under photoorganoheterotrophic conditions. Indeed, previous studies reported that the protein content of PPB can vary between 45% and 75% [19]. This result was predictable, since, in this study, the process was conducted under photo fermentative conditions instead of photoorganoheterotrophy.…”
Section: Resultsmentioning
confidence: 57%
“…The maximum protein percentage of 34% is lower compared to studies conducted under photoorganoheterotrophic conditions. Indeed, previous studies reported that the protein content of PPB can vary between 45% and 75% [19]. This result was predictable, since, in this study, the process was conducted under photo fermentative conditions instead of photoorganoheterotrophy.…”
Section: Resultsmentioning
confidence: 57%
“…In this perspective, biological treatments are desirable due to relatively low energy inputs. Recently, anaerobic treatment using PNSB has received considerable research attention [2][3][4]. They are considered favorable due to their unique metabolic features.…”
Section: Introductionmentioning
confidence: 99%